The Effect of Transportation Hubs in the Canadian Economic Context - Fournier, Elisabeth (Université d'Ottawa | University of Ottawa, 2017)
This paper analyzes the effect of transportation hubs on economic centrality and four economic and social welfare variables. To do so, we construct the economic centrality variable using a weighted-network approach. We then study its determinants, focusing on whether transportation hubs have an impact on the economic integration of a province. We infer that transportation hubs do have a positive effect on economic centrality. These determinants are then implemented in the analysis of gross domestic product (GDP) per capita, life expectancy, share of the labor force with a secondary education, and infant mortality rate. Our results show that life expectancy and share of the labor force with a secondary education are both positively affected by transportation hubs. On the other hand, we discover that not all methods of transportation have a positive impact on GDP per capita. Lastly, we find that some, but not all, of the determinants of economic centrality explain infant mortality rates.